Pengembangan Dakon Interaktif pada Materi Thaharah di SDN Sumbersari 2 Megaluh Jombang - Fajar Sukma Nasrullah; Ospa Pea Yuanita Meishanti (Lembaga Yasin AlSys, 2026)
Islamic Religious Education (PAI) learning on thaharah material in elementary schools is still dominated by lecture methods and the use of textbooks, resulting in relatively low student involvement in the learning process. Thaharah material, which is conceptual in nature and requires direct practice, causes some students to experience difficulties in understanding the types of impurities, purification tools, and the correct procedures for purification. This study aims to develop Interactive Dakon media on thaharah material at SDN Sumbersari 2 Megaluh Jombang and to determine the level of feasibility and attractiveness of the developed media. This study used a Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of one material expert, one media expert, and 13 fifth-grade students at SDN Sumbersari 2 Megaluh Jombang. Data were collected through expert validation sheets and student response questionnaires, then analyzed using a five-point Likert scale and a percentage formula. The results of the study show that the Interactive Dakon media obtained material expert validation of 79% in the feasible category and media expert validation of 95% in the highly feasible category. Student responses showed a very high level of attractiveness, with several indicators reaching 100% and other indicators reaching 92.3%, which falls into the highly attractive category. The conclusion of the study affirms that Interactive Dakon media is feasible for use in PAI learning on thaharah material because it can provide a more concrete, interactive, engaging, and enjoyable learning experience. The implications of this study indicate that the use of traditional games as learning media can serve as an innovative alternative to increase student involvement while integrating elements of local culture into PAI learning in elementary schools.